Apples galore! - O'Connor, Jane (O'Connor, Jane. Fancy Nancy., 2013)
Embarking on a field trip to an apple-picking farm, Nancy enjoys the fancy autumn colors she observes in the orchard and resolves to find a perfect Gala apple for her father but fears the fruit of her choice is too far out of reach.